Statement complementing the EFSA Scientific Opinion on application (EFSA‐GMO‐NL‐2009‐75) for placing on the market of genetically modified oilseed rape Ms8 × Rf3 × GT73 and subcombinations, which have not been authorised previously (i.e. Ms8 × GT73 and Rf3 × GT73) independently of their origin, for food and feed uses, import and processing, with the exception of isolated seed protein for food, under Regulation (EC) No 1829/2003), taking into consideration additional information. (30th July 2020) - ; Naegeli, Hanspeter; Bresson, Jean‐Louis; Dalmay, Tamas; Dewhurst, Ian Crawford; Epstein, Michelle M; Firbank, Leslie George; Guerche, Philippe; Hejatko, Jan; Moreno, Francisco Javier; Mullins, Ewen; Nogué, Fabien; et al.
Abstract: The EFSA Panel on Genetically Modified Organisms (GMO) previously assessed oilseed rape Ms8 × Rf3 × GT73 and its subcombinations Ms8 × GT73 and Rf3 × GT73 according to the scope as defined in the application EFSA‐GMO‐NL‐2009‐75, and was not in the position to complete the safety assessment of products rich in protein, such as rapeseed protein isolates or products of this nature in animal feeding. Following a mandate from the European Commission, the GMO Panel assessed a 28‐day toxicity study in mice with the glyphosate oxidoreductase (GOXv247) protein, provided to complement information related to application EFSA‐GMO‐NL‐2009‐75 for the placing on the market of oilseed rape Ms8 × Rf3 × GT73 and its subcombinations Ms8 × GT73 and Rf3 × GT73, for food and feed uses, import and processing, with the exception of isolated seed protein for food. The 28‐day toxicity study on Escherichia coli‐ produced GOXv247 protein did not show adverse effects in mice, at the gavage doses up to 1000 mg/kg body weight (bw) per day. Taking into account its previous assessment on EFSA‐GMO‐NL‐2009‐75 and the outcome of the 28‐day toxicity study in mice with the GOXv247 protein provided in this mandate, the GMO Panel, based on a weight of evidence approach, concludes that food and feed containing, consisting and produced from genetically modified oilseed rape Ms8 × Rf3 × GT73 and its sub combinations Ms8 × GT73 and Rf3 × GT73, are as safe as its conventional counterpart, according to the scope as defined in the application EFSA‐GMO‐NL‐2009‐75. Abstract : This publication is linked to the following EFSA Journal articles: http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2020.6199/full